PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, PROFITABILITAS, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN INDEKS LQ45 (2015-2019) - Jeremy Fidelio Djie Hutama (Ma Chung Press, 2021)
This study aims to examine the effect of capital structure, company size, profitability, and dividend policy on firm value at companies listed on the LQ45 index in 2015 - 2019. The amount of data that fits the sample criteria is 85 data. This study uses multiple linear regression analysis to test the effect of each variable. The results showed that the capital structure has a positive effect on firm value because the higher the debt value or the capital structure of a company, the higher the firm's value. Firm size also has a positive effect on firm value because the larger the company size, the greater the firm value. The profitability of a company also has a positive effect on firm value. Dividend policy also has a positive effect on firm value. Theoretically, this study is in accordance with the pecking order theory which states that companies with high debt levels and good management levels will increase the firm value of the company. A company can increase its firm value by paying attention to its debt level or capital structure, increasing company size, increasing profitability, and increasing dividends given to investors.